Von Bismarck bis zur Schmach von Versailles - Herrmann, Curt; Ocklitz, Oskar; Vogel, Georg; Scheil, Hans; Wuttke, Gerhard; Ertel, Max (Schriften zu Deutschlands Erneuerung / Sachband, 1935)
Enthält Nr. 2, 3, 5, 11, 21a/b/c und 42 der Schriften zu Deutschlands Erneuerung